Parishin A Inhibits Oral Squamous Cell Carcinoma via the AKT/mTOR Signaling Pathway - Lei Ma; Zhibin Liu; Eungyung Kim; Ke Huang; Chae Yeon Kim; Hyeonjin Kim; Kanghyun Park; Woo-Sung Kwon; Sang In Lee; Yong-Gun Kim; Youngkyun Lee; So-Young Choi; et al. (MDPI AG, 2024)
Background: Oral squamous cell carcinoma (OSCC) is an aggressive cancer with limited treatment options. Parishin A, a natural compound derived from Gastrodia elata, possesses multiple therapeutic properties. However, its effects on OSCC remain unexplored. Purpose: This study explores the anti-cancer potential of Parishin A on OSCC and its mechanisms. Methods: OSCC cell lines YD-10B and Ca9-22 were treated with varying Parishin A concentrations. Cell viability was detected using the CCK-8 assay, and colony formation was evaluated in agarose gel. Migration and invasion ability were assessed through wound healing and Matrigel invasion assays. The protein expression levels involved in the PI3K/AKT/mTOR signaling pathway and epithelial-mesenchymal transition (EMT) markers were examined via Western blotting. Results: Parishin A inhibited OSCC cell viability in both dose- and time-dependent manners, with significant reductions at 20, 40, 60, and 80 μM, without affecting normal human gingival fibroblasts. Colony formation decreased substantially at ≥40 μM higher Parishin A concentrations in a dose-dependent manner. Also, migration and invasion assays showed significant suppression by Parishin A treatment concentration ≥40 μM in a dose-dependent manner, as evidenced by decreased wound closure and invasion. Western blot analyses revealed increased E-cadherin levels and decreased N-cadherin and vimentin levels, suggesting EMT inhibition. Parishin A also decreased the phosphorylation levels of PI3K, AKT, and mTOR. Conclusion: Collectively, these findings support the potential of Parishin A as an anti-OSCC agent.